The impacts of electric vehicles and heat pumps load profiles on low voltage distribution networks in Great Britain by 2050 - Oliyide, Rilwan O.; Cipcigan, Liana M. (International Multidisciplinary Research Journal, 2021)
The impacts of uptake and electricity load profiles of Electric Vehicles (EVs) and Heat Pumps (HPs) on the low voltage (LV) distribution networks were analyzed. The United Kingdom (UK) has a legally mandated policy concerning reduction of greenhouse gasses (GHGs) emissions. Therefore, the integration of low carbon technologies (LCTs) especially EVs and HPs at the LV networks is expected to increase in the drive to reducing the GHGs emissions. Future uptake scenarios, adapted from the National Grid studies, of EVs and HPs were developed for a real and typical urban LV distribution network in Great Britain (GB). Gridlab-D, an agent-based power system simulation software, was used to model the LV distribution network. The model was run for four different scenarios considering seasonal load profiles and projected EVs and HPs uptakes for each of the year 2020, 2030, 2040 and 2050 respectively. The results were analyzed in terms of transformer loading, voltage profiles of the feeders, and the ampacity loading of the cables for the different scenarios of the years.